PERFORMANCE OF PUBLIC SERVICES IN LAND OFFICE HULU SUNGAI SELATAN DISTRICT - Arlan, Agus Sya’bani (PPPM STIA Amuntai, 2020)
Performance is the work result in quality and quantity that can be achieved by an employee in carrying out his main duties and functions as an employee in accordance with the responsibilities assigned to or assigned to him. The performance of public services at the Land Office of Hulu Sungai Selatan Regency is basically a form of service accountability in the land sector for the people in Hulu Sungai Selatan Regency in accordance with the vision and mission it carries. The purpose of this study is to determine the performance of public services that have been implemented by the Land Office of Hulu Sungai Selatan Regency, and to determine the factors inhibiting the performance of public services provided by the Land Office of Hulu Sungai Selatan Regency, and to analyze public service performance models in the Office. Hulu Sungai Selatan Regency Land. This research uses a qualitative approach with qualitative descriptive research type. The technique of collecting data by means of interviews, observation and documentation, with the technique of determining informants purposively so that there are 10 informants. As well as data analysis techniques using data reduction, data presentation and verification. The performance of public services at the Head of Land Affairs Office of Hulu Sungai Selatan Regency shows that the value is already good, with descriptions or details, namely that there are 2 (two) indicators that get good points, and 4 (four) indicators score quite good, and 4 (four) indicators get points yet / no / not good. The responsiveness subvariable on the indicators of agenda setting and service priorities is quite good in regulation, direction and implementation, and indicators of developing service programs are quite good. The responsibility sub-variable on the indicators of the easy service administration process is good, as well as the indicators for fast and precise administrative processes that are also good. In the accountability subvariable, the public accountability indicator is quite good, and the service process openness indicator is not good. The productivity sub-variable for the total production indicator is not good, and the quality production indicator is also not good, the service performance sub-variable in the service apparatus attitude indicator is quite good, and in the analysis indicator the results of public satisfaction are not good. The inhibiting factors for public services at the Land Office of Hulu Sungai Selatan Regency are caused by: the community, the lack of a process of socialization and legal counseling to the community, bureaucracy, facilities and infrastructure, and law enforcement. Supporting factors are the availability of reliable Human Resources in several fields / divisions and the support of the Central Government and Regional Government in the form of regulations. Performance models of the Land Office of Hulu Sungai Selatan Regency in public services in its territory, namely in maximizing the mass certification program through Computerized Land Office (KKP) programs, People's Service for Land Certificates (Larasita) and has continued in the form of Complete Systematic Land Registration (PTSL) ), and conduct legal education in the land sector, especially regarding the registration of land rights and public services as a form of community service. In an effort to improve the performance of public services at the Land Office of Hulu Sungai Selatan Regency, the author provides the following suggestions: The government needs to be more intensive in providing counseling and outreach to the community through both printed and electronic media in order to guarantee legal certainty for their land rights. Increase the budget for the implementation of mass land rights certification without charge or for free or in other public services.